How important is perception of safety to park use? A four-city survey. (September 2016) - Lapham, Sandra C; Cohen, Deborah A; Han, Bing; Williamson, Stephanie; Evenson, Kelly R; McKenzie, Thomas L; Hillier, Amy; Ward, Phillip
Our purpose was to determine the relative importance of individual- and park-related characteristics in influencing both local park use and specific engagement in active sports, walking and sedentary pursuits. We surveyed 3815 adults living within 0.80 km of one of 24 study parks in four US metropolitan areas. Chi-square statistics and baseline-category logit models examined how perceived safety and park characteristics were related to park visitation and types of park activities, controlling for city, individual and park characteristics. Survey participants who perceived the parks as safe (88%) had 4.6 times the odds (95% CI 3.5–6.0) of reporting having visited the study park. Men and African Americans were more likely, and older individuals and those who self-reported being in fair or poor health less likely to perceive parks as safe. Parks having low incivilities scores and those with four or more different facilities, such as tennis courts, swimming pools, basketball courts, etc., were more likely than parks with fewer facilities to be perceived as safe. While park facilities had a much smaller odds ratio for predicting park visits (1.8), it affected 70% of the population. The implication is, if these associations are causal, modifying park facilities may have a greater population impact than improving perceptions of park safety. Our findings are consistent with studies suggesting that increasing the variety of park facilities and offering more organised activities may encourage physical activity among specific target groups.